Suppression of the Lytic and Bactericidal Effects of Cell Wall-Inhibitory Antibiotics - Lopez, Ruben (1976)
The bacteriolytic effect of beta-lactam antibiotics on Bacillus subtilis and on Streptococcus pneumoniae was found to be a function of the pH; lysis was suppressed if the pH of the pneumococcal culture was below 6.0 during penicillin treatment. In the case of B. subtilis, growth at pH 6.6 prevented penicillin-induced lysis. In pneumococci, the addition of trypsin to the growth medium also protected against lysis. The pH-dependent protection phenomenon resembled in several respects the antibiotic “tolerance” of pneumococci with a defective autolytic system. (i) At the pH nonpermissive for lysis, the bacteria retained their normal sensitivity to beta-lactam and to other cell wall inhibitors; however, instead of lysis, the drug-treated bacteria simply stopped growing. Loss of viability of the cells was also greatly reduced. (ii) Protection against lysis was independent of the dose and chemical nature of the cell wall inhibitors. (iii) The protection effect was reversible; lysis and loss of viability could be triggered by a postincubation of the drug-treated bacteria at the pH permissive for lysis.